2020
DOI: 10.1038/s41598-020-78847-5
|View full text |Cite
|
Sign up to set email alerts
|

Effect of extraction temperature and solvent type on the bioactive potential of Ocimum gratissimum L. extracts

Abstract: Ocimum gratissimum is a shrub that belongs to the Lamiaceae family of plants. Despite the known biological activities and ethnomedicinal applications, comparative evaluation of the effects of different extraction techniques on the chemical and bioactive properties of O. gratissimum extracts has not yet been performed. This study adopted different analytical techniques to determine the effect of extraction temperature and solvent type on the phytochemical and bioactive properties of O. gratissimum extracts. Che… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
38
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(41 citation statements)
references
References 32 publications
3
38
0
Order By: Relevance
“…Compounds present in the essential oil of O. gratissimum include hydrocarbonated monoterpenes such as camphene, α-thujene, α-pinene, sabinene, β-pinene, β-myrcene, α and β-phellandrene, δ-3-carene, limonene, α-terpinene, p-cymene, trans-β-ocimene, γ-terpinene, terpinolene, p-cymenene, and p-menthane-1,3,8-triene; oxygenated monoterpenes such as 1.8-cineole, cis-sabinene hydrate, linalool, trans-sabinene hydrate, trans-thujone, citronellal, umbellulone, borneol, terpinen-4-ol, p-cymen-8-ol, α-terpineol, thymol methyl ether, estragol, p-cymen-7-ol, thymol, and carvacrol; hydrocarbonated sesquiterpenes such as α-copaene, β-elemene, γ-elemene, β-caryophyllene, α-trans-bergamotene, α-humulene, β-bourbunene, α-guaiene, δ-cadinene, germacrene D, γ-selinene, β-selinene, α-selinene, (Z,E)-α-farnesene, and 7-epi-α-selinene; and oxygenated sesquiterpenes such as caryophyllene oxide, 1,2-epoxydehumulene, and 3,7-(11)-eudesmadiene, spathulenol ( Vieira et al., 2001 ; Pessoa et al., 2002 ; Lahlou et al., 2004 ; Tchoumbougnang et al., 2005 ; Lemos et al., 2005 ; Benitez et al., 2009 ; Kpoviessi et al. 2012 , 2014 ; Nguemtchouin et al., 2013 ; Aguiar et al., 2015 ; Mohr et al., 2017 ; Chimnoi et al., 2018 ; Melo et al., 2019 ; Onyebuchi and Kavaz, 2020 ; Essoung et al., 2020 ). The bioactive compounds identified from the essential oil of O. gratissimum as well as their structures and various biological activities are shown in Table 2 .…”
Section: Phytochemistrymentioning
confidence: 99%
“…Compounds present in the essential oil of O. gratissimum include hydrocarbonated monoterpenes such as camphene, α-thujene, α-pinene, sabinene, β-pinene, β-myrcene, α and β-phellandrene, δ-3-carene, limonene, α-terpinene, p-cymene, trans-β-ocimene, γ-terpinene, terpinolene, p-cymenene, and p-menthane-1,3,8-triene; oxygenated monoterpenes such as 1.8-cineole, cis-sabinene hydrate, linalool, trans-sabinene hydrate, trans-thujone, citronellal, umbellulone, borneol, terpinen-4-ol, p-cymen-8-ol, α-terpineol, thymol methyl ether, estragol, p-cymen-7-ol, thymol, and carvacrol; hydrocarbonated sesquiterpenes such as α-copaene, β-elemene, γ-elemene, β-caryophyllene, α-trans-bergamotene, α-humulene, β-bourbunene, α-guaiene, δ-cadinene, germacrene D, γ-selinene, β-selinene, α-selinene, (Z,E)-α-farnesene, and 7-epi-α-selinene; and oxygenated sesquiterpenes such as caryophyllene oxide, 1,2-epoxydehumulene, and 3,7-(11)-eudesmadiene, spathulenol ( Vieira et al., 2001 ; Pessoa et al., 2002 ; Lahlou et al., 2004 ; Tchoumbougnang et al., 2005 ; Lemos et al., 2005 ; Benitez et al., 2009 ; Kpoviessi et al. 2012 , 2014 ; Nguemtchouin et al., 2013 ; Aguiar et al., 2015 ; Mohr et al., 2017 ; Chimnoi et al., 2018 ; Melo et al., 2019 ; Onyebuchi and Kavaz, 2020 ; Essoung et al., 2020 ). The bioactive compounds identified from the essential oil of O. gratissimum as well as their structures and various biological activities are shown in Table 2 .…”
Section: Phytochemistrymentioning
confidence: 99%
“…The use of sugar syrup at a temperature of 60 • C resulted in the extraction of larger amounts of compounds, including antioxidants. Increasing the temperature of the extraction process usually results in an increased amount of extracted components [33]. ever, these relationships were weaker than in the case of ozone treatment duration.…”
Section: Antioxidant Activity Of the Syrupsmentioning
confidence: 89%
“…This study confirmed that BSE showed a stronger anti-obesity effect at a lower concentration than the 70% EtOH extract of previous studies [ 35 ]. Natural products show a difference in physiological activities, such as anti-obesity and anti-cancer effects, depending on the extraction conditions [ 53 , 54 , 55 ]. Through this study, it was confirmed that hot-water extraction was the optimal extraction condition for the development of healthy functional foods and drugs for the anti-obesity effect of barley sprouts.…”
Section: Discussionmentioning
confidence: 99%